COMPARISON OF INPOUCH TF KITS AND DIAMOND’S MEDIUM FOR TRICHOMONAS GALLINAE IDENTIFICATION IN DOMESTIC PIGEONS - A. Raza; M. F. Qamar (Journal of Animal and Plant Sciences, 2017)
Trichomonas gallinae parasitizes a variety of avian orders especially in domestic pigeons (Columba livia domestica, Order Columbiformes). A variety of methods have been reported for the identification of T. gallinae in pigeons. Diagnosis of T. gallinae was accomplished by microscopic examination of oropharyngeal swabs of pigeons (n=120, males=78, females=42) using microscopic examination of InPouch TF culture kits and cultures taken form modified Diamond’s medium during various incubation time periods after post inoculation (PI). Total 68% pigeons were found positive for T. gallinae by InPouch TF kit and 55% were with modified Diamond’s medium. Significant differences were found between incubation time of for InPouch TF kit (CI-99%, p=.001) and for modified Diamond’s medium (CI-99%, p=.000<α). No significant sex-related difference in diagnosis of T. gallinae was found for InPouch TF kit (p=.839) and for modified Diamond’s medium (p=.765). InPouch TF as more sensitive method for the diagnosis of T. gallinae infections was also found to be practically efficient than Diamond’s medium in recovering the parasite from specimens and may provide a readily available, low-cost substitute for the Diamond’s medium in Pakistan.
Keywords: InPouch TF kits; Diamond’s medium; Diagnosis